Utilizing Sand as Glaze in Agung Glazinia Ceramics - Gusti Ngurah Agung Dalem Diatmika; I Ketut Muka; I Nyoman Suardina (Institut Seni Indonesia Denpasar, 2022)
This study aims to practice the application of sand to the glaze which is intended to produce glazes with different colors for staining ceramics. Qualitative methods are used with the data collection process through observation, interviews, and documentation. To find out the results resulting from the use of sand to glaze, an experimental method is applied as a reference in this study. The process of making glaze with a mixture of sand is still the same as the process of making glaze in general, starting from preparing tools or materials, mixing materials, applying to burning to find out the results obtained. The sand can produce new effects such as melting glass melts on glazes with certain colors. Characteristics of sand that is difficult to melt produces its own texture from the sand that is mixed into the glass. Sand glaze is very suitable to be applied to ceramic media which needs different shades from the glaze color in general. In the future sand glaze can be one of the glaze options that are in great demand by the public because it can reduce the material costs of making glaze.